Less is More, or Not? On the Interplay between Bundles of Slack Resources, Firm Performance and Firm Survival - Paeleman, Ine; Vanacker, Tom (Journal of Management Studies, 2015)
ABSTRACTAlthough a significant body of research has investigated the independent effects of distinct types of slack resources, current theoretical and empirical work does not sufficiently clarify how bundles of slack resources affect firm outcomes. Drawing on the resource constraints literature and the slack literature, we investigate how distinct bundles of financial and human resource slack influence firm performance and survival. Using a sample of 4715 European information and communication technology firms, we show that neither parallel resource abundance (having slack in financial and human resources) nor parallel resource constraints (lacking slack in financial and human resources) are optimal for firm performance and survival. However, firms with selective constraints that combine slack in financial resources with constraints in human resources exhibit superior performance without decreased survival prospects. Taken together, this study extends current research by providing a more nuanced view of the relationships between slack resources, firm performance, and firm survival.